Influence of dietary proteins on cholesterol levels in albino rats - Devadasan, K., Ammu, K., Stephen, J. and (Fishery Technology, 2021)
Six groups of albino rats were fed identical diets, differing in their protein sources for sixty days. The protein sources used were fat free casein, defatted groundnut cake, and defatted fish powders from three species of fishes, namely, the fresh water fish Labeo rohita, the marine fishes, Rastrelliger kanagurta and Otolithus argenteus and marine prawns, Parapenaeopsis stylifera. After sixty days, the levels of cholesterol in the serum, liver and heart of the rats were estimated. The casein group recorded the highest level of cholesterol. Compared to casein, the groundnut protein was distinctly hypocholesterolemic. The fish proteins had a still greater cholesterol lowering ability. Of the proteins used in this study, the proteins of prawns had the maximum hypocholesterolemic effect. An attempt is made to correlate the behaviour of the proteins in this respect, with their respective amino acid compositions.